High intensity interval training alters substrate utilization and reduces oxygen consumption in the heart - Hafstad, A. D.; Boardman, N. T.; Lund, J.; Hagve, M.; Khalid, A. M.; Wisløff, U.; Larsen, T. S.; Aasum, E. (Journal of Applied Physiology, 2011)
Aims: although exercise training induces hypertrophy with improved contractile function, the effect of exercise on myocardial substrate metabolism and cardiac efficiency is less clear. High intensity training has been shown to produce more profound effects on cardiovascular function and aerobic capacity than isocaloric low and moderate intensity training. The aim of the present study was to explore metabolic and mechanoenergetic changes in the heart following endurance exercise training of both high and moderate intensity. Methods and Results: C57BL/6J mice were subjected to 10 wk treadmill running, either high intensity interval training (HIT) or distance-matched moderate intensity training (MIT), where HIT led to a pronounced increase in maximal oxygen uptake. Although both modes of exercise were associated with a 10% increase in heart weight-to-body weight ratio, only HIT altered cardiac substrate utilization, as revealed by a 36% increase in glucose oxidation and a concomitant reduction in fatty acid oxidation. HIT also improved cardiac efficiency by decreasing work-independent myocardial oxygen consumption. In addition, it increased cardiac maximal mitochondrial respiratory capacity. Conclusion: This study shows that high intensity training is required for induction of changes in cardiac substrate utilization and energetics, which may contribute to the superior effects of high compared with moderate intensity training in terms of increasing aerobic capacity.